Tumor Vasculature Targeted TNFα Therapy: Reversion of Microenvironment Anergy and Enhancement of the Anti-tumor Efficiency - Balza, Enrica; Carnemolla, Barbara; Orecchia, Paola; Rubartelli, Anna; Poggi, Alessandro; Mortara, Lorenzo (Current Medicinal Chemistry, 2020)
Tumor cells and tumor-associated stromal cells such as immune, endothelial and mesenchimal cells create a Tumor Microenvironment (TME) which allows tumor cell promotion, growth and dissemination while dampening the anti-tumor immune response. Efficient anti-tumor interventions have to keep into consideration the complexity of the TME and take advantage of immunotherapy and chemotherapy combined approaches. Thus, the aim of tumor therapy is to directly hit tumor cells and reverse endothelial and immune cell anergy. Selective targeting of tumor vasculature using TNFα-associated peptides or antibody fragments in association with chemotherapeutic agents, has been shown to exert a potent stimulatory effect on endothelial cells as well as on innate and adaptive immune responses. These drug combinations reducing the dose of single agents employed have led to minimize the associated side effects. In this review, we will analyze different TNFα-mediated tumor vesseltargeted therapies in both humans and tumor mouse models, with emphasis on the role played by the cross-talk between natural killer and dendritic cells and on the ability of TNFα to trigger tumor vessel activation and normalization. The improvement of the TNFα-based therapy with anti-angiogenic immunomodulatory drugs that may convert the TME from immunosuppressive to immunostimulant, will be discussed as well.
Keywords: chemotherapy